Importance and impact of guest satisfaction - Morvay Karakas , Klára (Applied Studies in Agribusiness and Commerce, 2014)
The service quality can be measured by the consumers’ satisfaction. Researchers assume that high quality satisfies the guests and satisfaction may increase their loyalty. The main goal of this article is to measure guest satisfaction and prove its positive impacts on Hungarian hotels’ performance. A comprehensive survey was made on the Hungarian wellness hotels in October 2012; the primary aim was to provide them suggestions to improve their quality on the base of guests’ feedback. A self-administered questionnaire were compiled and sent back by 815 respondents. The investigation examined the quality awareness, quality perception, guest satisfaction and the following behavioral intentions of domestic guests of spa hotels. It can be concluded that domestic guests are generally satisfied with the quality of services offered by Hungarian spa hotels. The message of this research is for hotel managers that the increase of guest satisfaction can be reached by the improvement of service quality, and not only with price discounts. It has been demonstrated that satisfaction is closely related to their willingness to return to the hotel, so it is an essential condition of loyalty.